Alteration of Right Ventricular-Pulmonary Arterial Coupling Before and After Decongestion in Non-Preserved Fraction Acute Heart Failure Patients at Adam Malik Hospital Medan - Brahmana, Andrew Timanta; Ketaren, Andre Pasha; Andra, Cut Aryfa; Lubis, Anggia Chairuddin; Haykal, Teuku Bob; Siregar, Yasmine Fitrina; Lubis, Hilfan Ade Putra; Purba, Joy Wulansari; Akbar, Nizam Zikri (Journal of Society Medicine, 2025)
Objective: To assess whether there is right ventricular-pulmonary artery (RV-PA coupling by tricuspid annular plane systolic excursion/pulmonary artery systolic pressure TAPSE/PASP) changes in determining the clinical results of decongestion in patients with acute heart failure (AHF) with non-preserved ejection fraction (non-HFpEF) before and after decongestive at Adam Malik Hospital Medan. Methods: This study is an observational study with a prospective approach and consecutively collected, in patients AHF with non-HFpEF at Adam Malik Hospital Medan in the period from September 2023 until November 2024d. The sample is an eligible population that meets the inclusion and exclusion criterias. Results: This study consisted total 44 subjects with majority of 37 men (75%), an average age of 61 years old. A total of 28 subjects (63.6%) had hypertension as comorbid. There were 33 people (75%) who had sinus rhythm. The most acute heart failure phenotype commonly found was acute decompensated heart failure (ADHF) with 21 subjects. The longest length of stay AHF was cardiogenic shock with a median of 9 days. A significant decrease in median heart (p 0.0001), tricpuspid valve gradient (TVG) examination showed a significant decrease in (p 0.0001), PASP examination had a significant decrease in the average (p 0.0001), RV-PA coupling showed a significant increment (p 0.0001). A significant relationship was found between RV-PA coupling changes and decongestion in all acute heart failure groups (p 0.005). No significant relationship between RV-PA coupling ratio with length of stay was found. Conclusion: There were differences found in RV-PA coupling as increment with significant value in complete and partial decongestion groups, with a RV-PA coupling cut-off value of 0.65 and sensitivity and specificity of 68.8% and 67.9%, respectively.